Emulsion Polymerization of Styrene with iso-octyl-3-mercaptopropionate as Chain Transfer Agent - Minari, Roque Javier (2008)
Four batch and unseeded emulsion polymerizations of styrene were investigated, which included isooctyl 3-mercaptopropionate (iOMP) as chain transfer agent (CTA). This compound was analyzed by 13C NMR and GC/ MS, resulting in a mixture of over 10 isomers. Because of different reactivities of the CTA isomers, the produced polystyrenes presented broad and bimodal molecular weight distributions (MWDs). A mathematical model was adjusted to the measurements, and the measured MWDs were adequately predicted when assuming the CTA as a binary mixture of high but different reactivities.